2019
DOI: 10.1111/ajt.15420
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia protects the liver from Small For Size Syndrome: A lesson learned from the associated liver partition and portal vein ligation for staged hepatectomy (ALPPS) procedure in rats

Abstract: Portal hyperperfusion and “dearterialization” of the liver remnant are the main pathogenic mechanisms for Small For Size syndrome (SFSS). Associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) induces rapid remnant hypertrophy. We hypothesized a similar increase in portal pressure/flow into the future liver remnant in ALPPS and SFSS‐setting hepatectomies. In a rodent model, ALPPS was compared to SFSS‐setting hepatectomy. We assessed mortality, remnant hypertrophy, hepatocyte prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 50 publications
1
19
2
Order By: Relevance
“…In recent work, our team proposed experimental evidence that the stimulation of angiogenesis at early time points during regeneration of a small remnant prevented SFSS-induced mortality. Maneuvers, such as hepatic artery ligation concomitant to extended hepatectomy or treatment with DMOG, a prolyl hydroxylase domain inhibitor that activates HIF-1α, triggered an early pro-angiogenic response and prevented the collapse of hepatic sinusoids in the small for size regenerating liver [ 122 ].…”
Section: Role Of Lsec In Extended Hepatectomymentioning
confidence: 99%
“…In recent work, our team proposed experimental evidence that the stimulation of angiogenesis at early time points during regeneration of a small remnant prevented SFSS-induced mortality. Maneuvers, such as hepatic artery ligation concomitant to extended hepatectomy or treatment with DMOG, a prolyl hydroxylase domain inhibitor that activates HIF-1α, triggered an early pro-angiogenic response and prevented the collapse of hepatic sinusoids in the small for size regenerating liver [ 122 ].…”
Section: Role Of Lsec In Extended Hepatectomymentioning
confidence: 99%
“…Furthermore, the patient developed reversible liver failure even if graft function was significantly increasing. The functional competition among the native liver and the auxiliary graft was investigated in the past 17,18 in cases of metabolic liver disease transplanted with auxiliary partial graft; this amount of knowledge was recently improved through the scientific advancements on liver partition and portal vein ligation during staged hepatectomy 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Although preliminary studies have shown that mitochondrial function, hypoxia signals, and the pathways above are involved in ALPPS-induced regeneration, there is a lack of robust evidence to support the causality (7)(8)(9)(10)15). A deeper understanding of the activation of HSCs and the JNK1/IHH axis has been demonstrated as the first example of an ALPPS-induced molecular event associated with unprecedented regenerative acceleration (7,16).…”
Section: Discussionmentioning
confidence: 99%